2011
DOI: 10.1051/medsci/201127182
|View full text |Cite
|
Sign up to set email alerts
|

Imagerie fonctionnelle cérébrale appliquée à l’analyse des phénomènes douloureux

Abstract: Au début des années 1990, la connaissance des circuits de la douleur était fondée essentiellement sur les données issues de l'expérimentation animale. De rares cas de lésions étudiées en post mortem, ou par scanner ou IRM (imagerie par résonance magnétique) chez l'homme victime d'anomalies de la perception douloureuse, avaient permis de progresser dans la connaissance des mécanismes cérébraux conduisant à la douleur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2011
2011
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
0
4
0
2
Order By: Relevance
“…The neuro-imaging work during the last three decades have shown the SII and insular areas to be key pain integration areas [25]. In fact, a recent combined MEG-fMRI study by Mochizuki et al confirmed that itch signals are mainly located in the secondary somatosensory cortex (SII)/insula, which were also activated in the fMRI experiment by the itch stimuli[6], [26].…”
Section: Discussionmentioning
confidence: 98%
“…The neuro-imaging work during the last three decades have shown the SII and insular areas to be key pain integration areas [25]. In fact, a recent combined MEG-fMRI study by Mochizuki et al confirmed that itch signals are mainly located in the secondary somatosensory cortex (SII)/insula, which were also activated in the fMRI experiment by the itch stimuli[6], [26].…”
Section: Discussionmentioning
confidence: 98%
“…An update published by Peyron and Faillenot [17] demonstrated that the rostral cingulate cortex as well as medial prefrontal areas are associated with activation in pain relief. They postulate that activation in these areas may correlate with the magnitude of pain relief, activation of the periaqueductal gray and possible release of endogenous opioids [17]. …”
Section: Discussionmentioning
confidence: 99%
“…Bogod et al [28] targeted the subgenual cingulate gyrus in 4 patients with treatment-resistant depression and were able to demonstrate improved cognitive abilities using serial neuropsychological evaluations. Taken together, this body of literature leads to the conclusion that anterior cingulate cortical cells play an important role in mediating many of the higher cortical responses to pain [17,26]. …”
Section: Discussionmentioning
confidence: 99%
“…Avant le début du traitement, chaque patient a bénéficié d'une imagerie par résonnance magnétique fonctionnelle (IRMf) afin d'enregistrer l'activité cérébrale au repos [11] (➜). À la fin de la période de traitement, les patients dont les douleurs ont diminué d'au moins 20 % ont été qualifiés de répondeurs au placebo ; les autres de non-répondeurs ( Figure 1A).…”
Section: Nouvelleunclassified